Pengembangan Modul Pembelajaran Vokasional pada Program Paket C di PKBM Melati Ogan Ilir - Nengsih, Yanti karmila; Helmi, Henny; Rantina, Mahyumi; Nurrizalia, Mega (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2019)
This study aims to develop a product in the form of Vocational Learning Module Development in the Package C Program at the Community Learning Activity Center Melati Ogan Ilir. This development research was carried out by referring to the steps to develop the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The research trial subjects consisted of experts, and the target of product users, namely tutors, were taken using purposive sampling method, so the research subjects were obtained, namely 2 experts, and 2 tutors package C program. This research was conducted by testing research products until the small group test stage and the data obtained were analyzed descriptively. The results showed that: The package C vocational learning module was judged to be very feasible to be used by residents of learning and teachers or package C tutors in the implementation of vocational learning especially traditional dance arts. The level of use of package C vocational learning modules high for use by study residents.